Effectiveness of Earwigs (Euborellia annulipes (Lucus)) in Controlling the Aphid (Aphis craccivora Koch) in Pak Choi - บุญเทียม, ปิยะ; เสนาสิงห์, วรางรัตน์; เทียนกล่ำ, อังคณา เทียนกล่า (Journal of Vocational Education in Agriculture, 2019)
The purpose of this study was to examine the effectiveness of earwigs (Euborellia annulipes (Lucus)) in the control of aphids in pak choi (Brassica rapa subsp. Chinensis) by comparing rates of one earwig per plant (Treatment 1) and two earwigs per plant (Treatment 2) on plants at economic injury level (the number of aphids greater than one per leaf) seven days after transplanting. The aphid populations were counted 5, 7 and 10 days after the release of the earwigs. By comparing the means of the populations using t-test, it was found that there was no statistically significant difference at 95 % between both treatments. At 5, 7 and 10 days after the release of the earwigs, the average numbers of aphids were 0.36, 0.00 and 16.23, respectively in treatment 1 and 0.40, 0.37 and 51.92, respectively in Treatment 2. Using the percentage of correction between the aphid counts after 5, 7 and 10 days in both treatments, it was found that percentage correction from the first count was a decrease (- 707.50) and the percentage corrections from the second and third count were increases (100 and 29.96). However, the average correction from all releases was a decrease (-192.51). This indicates that a rate of two earwigs per plant can control the aphids in pak choi more effectively than a rate of one earwig per plant.